2015
DOI: 10.1111/bjet.12325
|View full text |Cite
|
Sign up to set email alerts
|

3D face model dataset: Automatic detection of facial expressions and emotions for educational environments

Abstract: Emotion detection using facial images is a technique that researchers have been using for the last two decades to try to analyze a person's emotional state given his/her image. Detection of various kinds of emotion using facial expressions of students in educational environment is useful in providing insight into the effectiveness of tutoring sessions. Robust recognition with conventional 2D cameras is still not possible under realistic conditions, ie, in the presence of variation in lighting and illumination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…We have tried to include the diagnostic and therapeutic methods that have been published in scientific journals, but the data, including quantitative and qualitative information, are limited, which causes an important drawback of this paper. For the summary of these methods see Table . What we can expect in the future is a rapid growth of use of modern technologies, such as VR, augmented reality, and interactive systems based on game consoles, in therapy enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have tried to include the diagnostic and therapeutic methods that have been published in scientific journals, but the data, including quantitative and qualitative information, are limited, which causes an important drawback of this paper. For the summary of these methods see Table . What we can expect in the future is a rapid growth of use of modern technologies, such as VR, augmented reality, and interactive systems based on game consoles, in therapy enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this article is to investigate the physical characteristics of emotion expressiveness across these modalities in several psychiatric conditions, and to examine how new technology can support clinical practice. A summary of the most important methods and studies on emotion expression assessment methods is presented in Table . The idea that emotions are innate, unlearned responses associated with a complex set of movements affecting the face, body, and speech traces back to Darwin, who suggested that the way in which we express emotions has evolved from emotional expression in other animals.…”
Section: Summary Of Emotion Expression Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be in terms of different facial expressions, posture and movements due to co‐occurring neurological differences and different use of eye gaze in those with autistic tendencies. Self‐annotation of recordings (eg, Chickerur & Joshi, 2015) was not appropriate in our study due to the ability of the participants. Therefore, rather than use a method established for main stream learners (eg, BROMP, Ocumpaugh, Baker, & Rodrigo, 2012), in order to determine the affective state of students with ID, teachers and trained researchers familiar with the students annotated recordings of them working on educational materials on a variety of platforms (desktop, mobile devices and educational robots).…”
Section: An Adaptive Learning System Based On Affect Sensing (The Matmentioning
confidence: 99%
“…However, as the authors in [23] argue, using conventional 2D cameras lacks robustness as this kind of cameras are subject to poor illumination and changes in lighting conditions. In response, they propose the use of Kinetic cameras as these are able to capture depth, and produce a dataset containing 3D models of several participants performing multiple facial expressions.…”
Section: Affective Datasetsmentioning
confidence: 99%